A Prospective Study of Overuse Knee Injuries Among Female Athletes With Muscle Imbalances and Structural Abnormalities - Devan, Michelle R. (National Athletic Trainers' Association, Inc., 2004)
OBJECTIVE: To prospectively examine the influence of hamstring-to-quadriceps (H:Q) ratio and structural abnormalities on the prevalence of overuse knee injuries among female collegiate athletes. DESIGN AND SETTING: We used chi-square 2 × 2 contingency tables and the Fischer exact test to examine associations among H:Q ratios, structural abnormalities, and overuse knee injuries. SUBJECTS: Fifty-three apparently healthy women (age = 19.4 ± 1.3 years, height = 167.6 ± 10.1 cm, mass = 65.0 ± 10.0 kg) from National Collegiate Athletic Association Division I women's field hockey (n = 23), soccer (n = 20), and basketball teams (n = 10) volunteered. MEASUREMENTS: The H:Q ratio was determined from a preseason isokinetic test on a Biodex system at 60°/s and 300°/s. We measured athletes for genu recurvatum and Q-angles with a 14-in (35.56-cm) goniometer. Iliotibial band flexibility was assessed via the Ober test. RESULTS: Ten overuse knee injuries (iliotibial band friction syndromes = 5, patellar tendinitis = 3, patellofemoral syndrome = 1, pes anserine tendinitis = 1) occurred in 9 athletes. The H:Q ratio below the normal range at 300°/s (P = 0.047) was associated with overuse knee injuries, as was the presence of genu recurvatum (P = 0.004). In addition, athletes possessing lower H:Q ratios at 300°/s and genu recurvatum incurred more overuse knee injuries than athletes without these abnormalities (P = 0.001). CONCLUSIONS: The presence of genu recurvatum and an H: Q ratio below normal range was associated with an increased prevalence of overuse knee injuries among female collegiate athletes. Further investigation is needed to clarify which preseason screening procedures may identify collegiate athletes who are susceptible to overuse knee injuries.